Balancing chemical fertiliser application for optimal maize yield and environmental safety - Osman, Magdoline; Kuunya, Ronald; Alrasheed, Raina; Wasikoyo, Erastus; Tamás, András; Illés, Árpád; Ragán, Péter; Rátonyi, Tamás (Acta Agraria Debreceniensis, 2026)
Chemical fertilisers play a crucial role in enhancing maize productivity by supplying essential nutrients, particularly nitrogen, phosphorus, and potassium. However, excessive and imbalanced application of these fertilisers may result in soil degradation and environmental pollution. This review presents a comprehensive, bibliometric, and literature-based analysis of research on the balanced use of chemical fertilisers in maize production, spanning 2000 to 2025, and uses VOSviewer 1.6.20 as the analytical tool. The study analysed data from the Web of Science to examine publication trends, the configuration of keyword networks, and the dynamics of international research collaborations. The Mann-Kendall test revealed a significant positive trend (p = 0.001) in the volume of publications focused on chemical fertiliser balancing, with a coefficient of determination (R²) of 0.5153. A total of 549 relevant studies were identified globally, with no language restrictions applied, indicating sustained growth in research output over time. Field studies demonstrate that reducing chemical fertiliser use by up to 25% when combined with biological amendments can maintain or enhance yields across diverse agroecological conditions. The emphasis is placed on sustainable fertilisation practices that balance productivity and environmental safety, highlighting challenges and future directions for adoption. Balanced fertiliser management is crucial for sustainable maize production systems, which simultaneously contribute to food security and environmental conservation. This study is significant as it systematically maps the evolution and current state of research on balanced chemical fertiliser use in maize production, providing valuable insights into publication trends, collaborative networks, and practical agronomic outcomes. Despite the progress, there remains a significant gap in region-specific guidelines and long-term impact assessments of integrated fertiliser management practices, which future research should address to optimise sustainable maize production tailored to diverse agro-ecological zones.